An amphiphilic peptide with unnatural amino acids as an alignment medium for RDC measurements - Yishen Wang; Haizhi Yin; Yanling Yang; Zheng-Hui Li; Gao-Wei Li; Xinxiang Lei (Magnetic Resonance Letters)
The multiple oligopeptides have been regarded as promising alignment media due to their structural diverseness and tendency for self-assembly in solution. Herein, an assembled amphiphilic peptide alignment medium, i.e., C15–CONH-Phg-Phg-IIIKK-CONH2 with unnatural amino acids for the determination of anisotropic parameters of NMR is introduced. The amphiphilic peptide can be self-assembled at low concentrations in DMSO and is stable and highly homogeneous. The NMR spectrum collected with the addition of the medium had fewer background signals. The utility of the acquired RDC data is demonstrated to determine relative configuration of three natural products, Helminthosporic acid, Estrone, and α-Santonin.